Interplay of Connexins and Pannexins in Tissue Function and Disease - Patricia Martin (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue is related to the 18th biannual International Gap Junction Conference (IGJC2017), which has been held at the Crowne Plaza Hotel, Glasgow and hosted by Glasgow Caledonian University, 29 July-3 August, 2017. This Special Issue, entitled "Interplay of Connexins and Pannexins in Tissue Function and Disease", focuses on six key state-of-the-art reviews, written by leads in the field on cutting edge topics and the latest developments in clinical trials in diverse organ systems. A further 14 original articles contributed by delegates attending the meeting are also included and celebrate 50 years of Gap Junction Research. Topics: Connexins and Pannexins: • Trafficking, Assembly, Gating, and Protein-Protein Interactions • Roles in the Cardiovascular System • Roles in Tumorigenesis • Roles in Epithelial Tissue and Wound Healing • Connexin Therapy Translated to Clinic